Inscriptions of the Aulikaras and Their Associates - Balogh, Dániel (Beyond Boundaries, 2019)
The Aulikaras were the rulers of western Malwa (the northwest of Central India) in the heyday of the Imperial Guptas in the fifth century CE, and rose briefly to sovereignty at the beginning of the sixth century before disappearing from the spotlight of history. This book gathers all the epigraphic evidence pertaining to this dynasty, meticulously editing and translating the inscriptions and analysing their content and its implications.